HaloBin / Nur Husna Muhammad Sani - Muhammad Sani, Nur Husna (2020)
We are from Halo Sdn Bhd, proudly present our latest smart dustbin, HaloBin. HaloBin uses commercial waste dehydrator to evaporate moisture in wastes in order to eliminate bacteria growth that causes odour. Other than that, our product comes together with wastes compactor that will reduce the volume of wastes to provide extra space in one bag. This smart dustbin also has built in motion sensor that opens the lid when movement is detected. We target for buyers from middle class to upper class for our product. Our product requires users that pays attention to modern technologies and aesthetics as this dustbin is made with elegant structure. This product is going to attract high class individuals. We are confident that this product is able to expand its market amongst our target customers. The profit gained within 3 years of production is going to be feasible for the stability of this company. This is due to the technology that we provide in this product. Our target customers will be eager to get this product to complete the look of their space.